2021
DOI: 10.3390/ma14102539
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Method of Converting Ferrous Mill Scale Wastes into Superparamagnetic Nanoadsorbents for Water Decontamination

Abstract: The need to recycle and develop nanomaterials from waste, and use them in environmental applications has become increasingly imperative in recent decades. A new method to convert the mill scale, a waste of the steel industry that contains large quantity of iron and low impurities into a nanoadsorbent that has the necessary properties to be used for water purification is presented. The mill scale waste was used as raw material for iron oxide nanopowder. A thorough characterization was performed in each stage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…As an alternative to commercial iron-based salts, waste products from steel and iron industries can be used as precursors in synthesizing IONPs. Among the commonly used steel by-products for production of IONPs are mill scale [ [116] , [117] , [118] , [119] ], steel pickling liquor [ [120] , [121] , [122] ], electric arc furnace dust [ 123 , 124 ], iron waste powder [ 125 , 126 ], and others. A detailed review on generation of IONPs from steel wastes for removal of pollutants from water has been presented [ 92 ].…”
Section: Preparation Of Iron Oxide Nanoparticles For Applications In ...mentioning
confidence: 99%
“…As an alternative to commercial iron-based salts, waste products from steel and iron industries can be used as precursors in synthesizing IONPs. Among the commonly used steel by-products for production of IONPs are mill scale [ [116] , [117] , [118] , [119] ], steel pickling liquor [ [120] , [121] , [122] ], electric arc furnace dust [ 123 , 124 ], iron waste powder [ 125 , 126 ], and others. A detailed review on generation of IONPs from steel wastes for removal of pollutants from water has been presented [ 92 ].…”
Section: Preparation Of Iron Oxide Nanoparticles For Applications In ...mentioning
confidence: 99%
“…101 Moreover, mill scale from the steel industry produced during the milling process consists of iron oxide and this waste can be converted to valuable secondary material, such as iron oxide nanoparticles through a reduction process, either by using hydrogen, microwave heating, or by applying solution-based techniques. 102 Rahman et al also reported that γ-Fe 2 O 3 nanoparticles from different iron-containing waste materials could simply be obtained by a simple chemical precipitation method using HCl, NaOH, and Na 2 CO 3 , followed by calcination. 103 Iron oxide nanoparticles also have been successfully fabricated from scrap iron waste using a simple one-step approach via an aqueous medium under alkaline conditions.…”
Section: Nanometer-sized Ironmentioning
confidence: 99%
“…Waste materials from steel plants such as slags, mill scale, and lean ores also can be used to synthesize α-Fe 2 O 3 , which then could be converted to γ-Fe 2 O 3 by the combustion method . Moreover, mill scale from the steel industry produced during the milling process consists of iron oxide and this waste can be converted to valuable secondary material, such as iron oxide nanoparticles through a reduction process, either by using hydrogen, microwave heating, or by applying solution-based techniques . Rahman et al also reported that γ-Fe 2 O 3 nanoparticles from different iron-containing waste materials could simply be obtained by a simple chemical precipitation method using HCl, NaOH, and Na 2 CO 3 , followed by calcination .…”
Section: Advance Fabrication Of Nanometer-sized Iron Oxides From Natu...mentioning
confidence: 99%
“…This approach has an easy-to-understand design and functioning, and it is reasonably priced. Many materials, such as carbon-based materials, various synthetic porous composites, naturally occurring inorganic minerals like clay or zeolites, and functionalized natural and synthetic polymers, have been rendered effective at removing organic and inorganic contaminants from polluted water samples [ 12 ].…”
Section: Introductionmentioning
confidence: 99%